EDUCAÇÃO E DITADURA MILITAR: RELATOS DA HISTÓRIA OFICIAL E A MEMÓRIA DE PROFESSORES (1964-1985) - Pinheiro, Claudio (2006)
They present research considers to analyse the occurred educational context in the period of the military dictatorship, searching to extract referryng historial and educational aspects to the period ( 1964 1985). It is carried through with degree as a research professors old of the public net of education of the city of Santo André (SP). It was opted to interviewing six professors (teachers) who had acted during this historical context. To ionvestigate, the historial metodológica boarding of qualitative matrix was used, choosing the memory as principal source of study. For in such a way, one appealed the contribuitions to it of Bosi (Memory and society: souvenirs of old, 1984), Thompson (The voice of Past, 1992), Romanelli (History of the Education in Brazil, 1978), Freitag (Been school and socity, 1980), Góes (The blow in the Education, 1996), Wedge (Education and Social Development in Brazil, 1977), Cardoso (For a critical one of the gift, 2001), Vieira (Been and social misery in Brazil, 1995), Minguili (Direction of School of 2º degree in the state of SP, 1984), Arelaro (The extension of basic education in Brazil, 1988), Teixeira (Politics and administration of teaching staff, 1988), Hilsidorf (History of the Brazilian education, 2005), Gadotti (Education and power, 2001), Full brother (Been military man and education in Brazil, 1990), Saviani (School and democracy, 1986), Saints (Teachers in times of changes, 2003). The worked hypotheses is concentrated in interpreting the position of the professors who had acted in the period in question, relative to the regimen politician whom if it installed in the coutry during this time, and of that it forms this reed echo in its teaching work. In the analysis of politico/social and educational the context, the revision was appealed to it that had supplied subsidies to understand and to show the voice of Dictatorship and Education.